Mind-mindedness in mothers of infants with excessive crying/sleeping/eating disorders - Licata-Dandel, Maria; Kristen-Antonow, Susanne; Marx, Sarah; Mall, Volker (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction Excessive crying, sleeping, and eating disorders are among the most prevalent mental health diagnoses in the first 3 years of life and involve significant health service use. Parents of infants with excessive crying/sleeping/eating disorders report high levels of stress, since they feel incapable of soothing and/or nurturing their baby. Infants' distress can lead to a breakdown in parents' mentalizing abilities and, more specifically, parental mind-mindedness in the parent-child interaction. Moreover, the signals of infants with excessive crying/sleeping/eating disorders tend to be equivocal and difficult to read. This also might contribute to lower parent-child interaction quality. Until now, parental mind-mindedness, which is regarded as a prerequisite for sensitivity, has not been investigated in mothers of infants with excessive crying/sleeping/eating disorders. We investigated whether mind-mindedness in mothers of infants with excessive crying, sleeping and/or eating disorders differed from a healthy control group. We supposed that mothers of infants with excessive crying/sleeping/eating disorders would use (1) less appropriate mind-related comments (AMRCs), and (2) more non-attuned mind-related comments (NAMRCs) than mothers in the control group. Methods Our sample consisted of 44 mothers and their infants who were patients in a socio-paediatric clinic in Germany. The children were diagnosed with excessive crying, sleeping and/or eating disorders according to DC:0-5 (= clinical group). The control group was composed of 64 healthy children and their mothers. Maternal mind-mindedness was coded during a free-play interaction. Results Results showed that mothers of infants with excessive crying, sleeping and/or eating disorders used both more AMRCs (p = .029) as well as more NAMRCs (p = .006) than mothers in the control group. Discussion The findings are discussed in terms of implications for interventions (e.g., enhancing mind-mindedness trough video-feedback).